(untitled) (Medico Legal Update, 2020)
Parkinson’s disease is a neurodegenerative progressive disorder end with independency for many years at late life, leading to great burden on patient and family life. The available treatment is symptomatic focused on improving life quality of the patient and it’s in need for good communication with the physician. So far there is no easy and practical way for follow up, thus we’ve designed the Parkinson’s disease follow up self-assessment scale aiming to detect ON and OFF time, it’s include PD manifestations, medications and medications adverse effects filled out by the patient family at home in order to mailing it to the physician, and intend to testing it by comparing the performance of patient family with expert staff in using the scale at hospital for 24 hours. Then enquiring about difficulty of using the same scale at home. A 44 PD patient were completed the study. All items accuracy filling out was 93.4% in compare to expert staff. Its mean degree of difficulty was 4/10 and among patients families only 29.54% consider it difficult to use. The ON and OFF time was detected precisely in 92.2% by follow up physician. The proposed scale is precise in detection ON an OFF time and not difficult to use.